Articular soft tissue injuries associated with mandibular condyle fractures and the effects on oral function. Issue 6 (June 2019) - Weinberg, F.M.; Speksnijder, C.M.; Forouzanfar, T.; Rosenberg, A.J.W.P.
Abstract: The majority of studies debating the optimization of treatment for condylar mandibular fractures focus on the bony aspect first. However, fractures of the mandibular condyle may go together with soft tissue injury of the temporomandibular joint. An electronic literature search for this topic was undertaken. Assessment of quality was carried out using the Quality Assessment Tool for Observational Cohort and Cross-Sectional Studies. Sixteen articles were included in this review. The reviewed literature showed that intracapsular fractures and dislocated condylar fractures result in more severe injuries. Serious injury to the disc and capsule of the temporomandibular joint is a contributing factor towards development of complications after closed treatment. The results of this review give an overview of the published studies focusing on articular soft tissue injuries caused by condylar mandibular fractures. Additionally, an overview of the magnetic resonance imaging (MRI) settings used to detect these injuries is provided. Until now, the relation between soft tissue injuries and type of condylar trauma and their influence on clinical outcome has been insufficiently investigated. Before considering reduction of soft tissues next to reduction of the fracture, more research is needed into the impact of soft tissue injuries on oral functioning, in which a uniform classification is used.